1996
DOI: 10.1180/minmag.1996.060.402.01
|View full text |Cite
|
Sign up to set email alerts
|

Supra-subduction zone ophiolites of Central Anatolia: geochemical evidence from the Sarikaraman Ophiolite, Aksaray, Turkey

Abstract: The Central Anatolian Crystalline Complex (CACC), situated between the northern and southern oceanic strands of Neotethys, contain a number of little-studied ophiolitic bodies of late Cretaceous age that have a bearing on the Mesozoic development of this region. The pillow lavas and sheeted dykes of the Safikaraman Ophiolite were originally a comagmatic differentiated series of vesicular, aphyric and olivine-poor, plagioclase-clinopyroxene phyric tholeiites, but now exhibit gmenschist facies assemblages. A set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 35 publications
0
62
0
1
Order By: Relevance
“…Göncüoğlu et al (2006) indicated that radiolarian evidence suggests that rifting of the Neotethys İzmir-Ankara Zone occurred in the Late Triassic and the İzmir-Ankara oceanic plate did not get subducted until the Cenomanian. Defining the formation of the supra-subduction zone (SSZ) type oceanic crust in the eastern part of the İzmir-Ankara Suture Belt, Göncüoğlu and Türeli (1993) and Yalınız et al (1996) accepted that the İzmir-Ankara oceanic basin began to close by intraoceanic subduction (Göncüoğlu and Türeli, 1993;Tüysüz et al, 1995;Göncüoğlu et al, 1997Göncüoğlu et al, , 2006Okay and Tüysuz, 1999). The oldest ages obtained from the amphibolites in the İzmir-Ankara Suture Zone were between 101 Ma (Harris et al, 1994;Göncüoğlu et al, 2006) and 90 Ma (Önen, 2003;Göncüoğlu et al, 2006).…”
Section: Regional Geologymentioning
confidence: 99%
“…Göncüoğlu et al (2006) indicated that radiolarian evidence suggests that rifting of the Neotethys İzmir-Ankara Zone occurred in the Late Triassic and the İzmir-Ankara oceanic plate did not get subducted until the Cenomanian. Defining the formation of the supra-subduction zone (SSZ) type oceanic crust in the eastern part of the İzmir-Ankara Suture Belt, Göncüoğlu and Türeli (1993) and Yalınız et al (1996) accepted that the İzmir-Ankara oceanic basin began to close by intraoceanic subduction (Göncüoğlu and Türeli, 1993;Tüysüz et al, 1995;Göncüoğlu et al, 1997Göncüoğlu et al, , 2006Okay and Tüysuz, 1999). The oldest ages obtained from the amphibolites in the İzmir-Ankara Suture Zone were between 101 Ma (Harris et al, 1994;Göncüoğlu et al, 2006) and 90 Ma (Önen, 2003;Göncüoğlu et al, 2006).…”
Section: Regional Geologymentioning
confidence: 99%
“…The lower unit comprises of tectonic accretionary wedge of older back-arc basin lithologies, including high-Ti mafic rocks. Yaliniz et al (1996) have divided the ophiolites of the region into two groups; western MOR Jurassic and eastern suprasubduction (SSZ) Cretaceous ophiolites. The SSZ features often comparable with younger back-arc basins worldwide (Pearce et al, 1994).…”
Section: General Geologymentioning
confidence: 99%
“…On the otherhand, ophiolitic masses are emplaced on the continental crust (Beyarslan & Bingöl, 2000;Parlak, Höck, Kozlu, & Delaloye, 2004;Parlak & Robertson, 2004;Robertson, 2002Robertson, , 2004Yalınız, Floyd, & Göncüoğlu, 1996. Tertiary units deposited in back-arc basins are most common (Aksoy, Türkmen, & Turan, 2005;Aktaş & Robertson, 1984;Cronin et al, 2000;Özkul & Kerey, 1996;Yazgan, 1984).…”
Section: Geological Frameworkmentioning
confidence: 99%